Effectiveness of Tahkim in Selangor Shariah Courts based on organizational effectiveness goal approach - Noor Fadhzana Mohd Noor; Mumtazah Narowi; Siti Amalina Ahmad Khairundin (Penerbit Universiti Kebangsaan Malaysia, 2023)
In general, tahkim (arbitration) is initiated by Shariah courts when marital disputes between parties have reached a severe phase, known as ‘shiqaq’. Through tahkim, the Hakam Keluarga or Hakam Panel are given absolute powers to pronounce the divorce to settle the disputes. In view of these, past literature has deemed tahkim to be an effective marital dispute resolution. However, empirical evidences to support this are still lacking. Despite the lack of past literature on tahkim, previous studies on the effectiveness of marital dispute resolutions, were conducted descriptively and without associating them with related conceptual frameworks on effectiveness. Considering this gap in the literature, this study aims to assess the effectiveness of tahkim based on the organizational effectiveness goal approach. Using thematic analysis on relevant laws on tahkim in Selangor and interviews, it was found that only some of the objectives of tahkim have been attained. In addition, it was found that the effectiveness of tahkim was perceived differently among the interviewees. As a result, it is plausible that the effectiveness of tahkim cannot be concluded. These findings also suggested that, assessing tahkim’s effectiveness using the goal approach may not be an accurate approach. In reference to the problems identified within the practices of tahkim, tahkim’s effectiveness may be well-assessed using other organizational effectiveness approaches. With these, the findings have provided alternatives to Islamic law scholars in interpreting organizational effectiveness within Syariah courts as well as providing alternative paradigms in perceiving effectiveness of a marital dispute resolution to help improve its quality towards the benefits of the disputing parties.